Upaya Peningkatan Kinerja SDM Pada Organisasi Pemuda Internasional (AIESEC UNJ) - Muhammad Ali Ramadhan (Jurnal Pembelajaran Inovatif, 2018)
This research aimed to analyze the needs that required in order to improve the performance of talent management department in AIESEC Universitas Negeri Jakarta. The model used is 3 phases Needs Assessment by Witkins and Altschuld. On each phases, there are some steps adjusted with the research purpose. The steps are reviewing the scope of research and main issue of performance problem, determining the ideal performance condition, identifying the gaps between ideal and actual condition, determining the performance needs, exploring the causes, and proposing alternative recommended solutions. The Instruments used are survey, interview, and documentation. The Informants consist of 1 department head, 2 divisions head, 8 staffs, 1 validator, and 2 expert matters. The result is, out of ten aspects, only four aspects are stated to be ideal related to the task and function implementation. Anything apart of that has gaps, resulting in performance needs that require to be addressed.